Carroll e Tenniel: le immagini di Alice - Castellani, Chiara (Studi sulla Formazione/Open Journal of Education, 2017)
The intent of this paper is to explore the importance of the images in Carroll’s work and the increase in meaning they bring to the written text. Therefore, some illustrations by Carroll in the manuscript Alice’s Adventures Under Ground and others by Tenniel in Alice’s Adventures in Wonderland are analysed, focusing on the similarities and differences between the author/artist and his illustrator.